EFFECT OF MICROWAVE RADIATION ON STRENGTH CAPPED POLYMER COMPOSITION MATERIALS WITH LIGHTNESS PROTECTIVE RETAINED COATING LOW-CYCLE LOADING - I. V. Zlobina (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives The analysis of the features of application of fiber-reinforced polymer composite materials (PCM) of different nature in the structural elements of aviation technology and methods of increasing the strength of their products. Method It is indicated on the positive effect on the strength of the bending stress and interlayer shear finish treatment of cured PCM in the microwave electromagnetic field. It is noted that the peculiarity of the elements of the skin of PCM is the presence in the surface layer of the built-in metal mesh, or lightning-proof coating (MFP), necessary to ensure the stability of structural elements to the effects of atmospheric electricity discharges. Result. The tests of the control and processed in the microwave electromagnetic field samples from PCM with MSP on low-cycle fatigue at the number of loading cycles-60 and strain amplitudes-10 mm. it was Found that in the control samples with the grid MEU primary crack appears after 6 cycles. After microwave processing, the samples retain their integrity, but the load causing the set deformation is reduced by 14% already on the 35th cycle. Conclusion Durability of samples with the heat-treated grid "Тekstilmash" and with a grid without heat treatment after influence of microwave electromagnetic field increases respectively by 59,5% and 71%. At the same time, the samples retain their integrity after 60 loading cycles, and the maximum stresses are reduced by 13.7% and 5.8%, respectively, compared to static tests. The limit of low-cycle fatigue increases  after microwave treatment from 37 to 210%.